The effect of internal branding on brand citizenship behavior and service performance - Gia-Tuong Tong; Gi-Du Kang (Journal of Innovation and Entrepreneurship)
Abstract Service is a fast-increasing industry in the global economy in general and in Vietnam in particular. Therefore, service companies need to recognize the importance of employees in service and cultivate specialized manpower and systematic internal brand management. The current study aims to explore and describe the role of internal customer orientation on service employee's perceptions and behaviors, tested a theory-driven framework of the multidimensional relationship between components in internal brand management and proposed suggestions for Vietnamese service organizations to enhance their competitive capabilities in the market. Using quantitative data analysis methods and SEM structural modeling, the study confirmed that the internal customer orientation can positively influence the brand identification and brand commitment of salespersons, helping them exhibit brand citizenship behavior towards the organization and enhance service performance. Besides, the crucial role of emotional exhaustion was investigated. In doing so, the research intends to implicate internal branding as a tool for enhancing the quality of the Vietnamese service industry.